11.Sınıf Öğrencilerinin Kimya Dersi Başarılarının Geleneksel ve Alternatif Ölçme Değerlendirme Açısından Karşılaştırılması - Kolomuç, Ali (Fırat University, 2016)
Bu Çalışma 2010-2011 eğitim öğretim yılında Trabzon’da iki farklı Anadolu lisesinde toplam 109 on birinci sınıf öğrencisi ile yürütülmüştür. Bu çalışmada Lisans Giriş Sınavı (LGS) konularını içeren; Kimya Dersi programının aynı kazanımlarına göre alternatif ölçme değerlendirme ve geleneksel ölçme değerlendirme soruları geliştirilmiş, öğrencilerin akademik başarıları karşılaştırılmıştır. Uygulamadan sonra öğrencilerin alternatif ölçme değerlendirme sorularına karşı bakış açılarını tespit etmek için öğrencilerin görüşleri alınmıştır. Çalışmada hazırlanan alternatif ölçme değerlendirme soruları 25 test sorusundan oluşmuş olup, testin geçerliliğini sağlamak için 5 kimya öğretmeni ve 5 akademisyene inceletilmiş, testin güvenirliliği 0,70 olarak bulunmuştur. Çalışmanın sonunda, öğrencilerin kimya dersi akademik başarılarının, alternatif ölçme değerlendirme başarısına göre daha başarılı olduğu tespit edilmiştir.

In this study it was carried out in Trabzon on two different Anatolian high schools in the academic year of 2010-2011 with total of 109 grade 11 students. The present study was improved according to same educational attainment in chemistry program based on comparison between alternative assessment and traditional assessment questions. After the application, students' perspectives were determined towards alternative assessment questions. Alternative assessment and traditional assessment questions composed of 25 test questions. Furthermore those 25 questions were got 5 chemistry teachers and 5 academics investigate to ensure the validity and reliability. As a result of the expert investigation, it was found that reliability of the test is such 0.70 that it was evaluated as reliable and valid data collection instrument. The-test, applied to compare, indicates that chemistry academic achievement of students were more successful than alternative assessment.
A comparison of grade 11 Students’ Success in the way of Traditional and Alternative Assessment